LISTENING TO CONVERSATIONS CONDUCTED FROM TELEPHONES AND OTHER TELECOMMUNICATION DEVICES, REMOVING INFORMATION TRANSMITTED THROUGH THEM: THE ROLE AND ESSENCE OF THE INVESTIGATIVE ACTION. (World Bulletin of Management and Law, 2024)
The scientific article considers the general concept and the very procedure for conducting an investigative action, such as listening to conversations conducted from telephones and other telecommunication devices, and removing information transmitted through them. In addition, the importance of this investigative action in the disclosure and investigation of serious and especially serious crimes is explained. Examples from foreign practice are also given.
Keywords: investigative action; operational search event; technical and procedural inspection